Not Ready for Prime Time: A Response to “Universal Basic Income: Policy Options at National, State, and Local Levels” - Canarie, Dave (Maine Policy Review, 2019)
Dave Canarie responds to Michael Howard’s commentary on universal basic income.
Keywords: UBI; poverty; inequality